Pengembangan Prototipe Pembangkit Listrik Tenaga Surya sebagai Media Pembelajaran pada Pokok Bahasan Energi Terbarukan - Azizah, Fitri; Khotimah, Siti Nurul (Jurnal Penelitian Pendidikan IPA, 2024)
Renewable Energy needs to be implemented in schools to build students' knowledge. This research aims to design a prototype of a Photovoltaic Power Plant (PLTS), which can be used as a medium for experimental high school physics activities. Besides that, the effect of light intensity on the power produced by the PLTS prototype was experimentally tested by observing temperature, humidity, and air pressure. The PLTS prototype is designed to be simple, with component selection (10 wp solar panels, SCC, batteries, lights and panel boxes) that are adapted to the learning media criteria, namely practical, durable, easy to use and able to demonstrate the concepts being taught. The PLTS prototype was tested when charging and discharging the battery. When charging the battery, the solar panel is tilted with a variety of tilt angles of 0º, 15º, 30º, 45º and 60º. When discharging the battery, lamps with varying powers are used, namely 3W, 5W, 7W and 9W. The research results show that the panel tilt angle is used to produce maximum voltage, current, and power when charging the battery, which is 30°. When the battery is discharged, a smaller lamp power can light the lamp for longer compared to a larger lamp power. In conclusion, the PLTS prototype can provide students with experience in conducting experiments and learning the application of physics concepts directly so that it can build students' knowledge and provide meaningful learning.